Liver iron excess in patients with hepatocellular carcinoma developed on viral C cirrhosis. Issue 5 (1st May 2000) - Chapoutot, C; Esslimani, M; Joomaye, Z; Ramos, J; Perney, P; Laurent, C; Fabbro-Peray, P; Larrey, D; Domergue, J; Blanc, F
Abstract : BACKGROUND: Liver iron deposits are frequent in viral C cirrhotic patients but their role is not well defined. AIMS: To investigate the effect of liver iron excess on the prevalence of hepatocellular carcinoma (HCC) in patients with viral C cirrhosis. METHODS: Hepatic iron was evaluated retrospectively using a semiquantitative method in liver biopsies of 104 viral C cirrhotic patients, 48 with HCC and 56 controls (HCC free). Corrected total iron score (0–60) was defined by the sum of three scores: hepatocytic iron score (0–36), sinusoidal iron score (0–12), and portal iron score (0–12), multiplied by 3/3, 2/3, or 1/3 according to the heterogeneous iron localisation in the nodules. RESULTS: After adjustment for known risk factors for HCC, regression analysis showed that iron deposits (corrected total iron score >0) were more frequent in HCC patients than in controls (odds ratio 4.94; 95% confidence interval 1.59–15.32; p=0.0056). The median of corrected total iron score was significantly higher in HCC patients than in controls (odds ratio 1.092; 95% confidence interval 1.01–1.13; p=0.021). This liver iron overload was sinusoidal (odds ratio 5.2; 95% confidence interval 1.82–15.11; p=0.0022). CONCLUSIONS: Liver iron deposition was more frequent and more important in viral C cirrhotic patients with HCC than in HCC free controls. Liver iron overload seems to contribute to the development of HCC in patients with viral C cirrhosis.